ZIKV: Epidemiology, infection mechanism and current therapeutics - Dahiya, Nisha; Yadav, Mahima; Singh, Hitesh; Jakhar, Renu; Sehrawat, Neelam (Frontiers in Tropical Diseases, 2023)
ZIKV is a flavivirus vector-borne disease that has affected 87 countries worldwide. Previously different outbreaks of ZIKV were reported around the world and declared a Public Health Emergency of International Concern. Zika virus possesses two modes of transmission i.e., either vector transmission or non-vector transmission. The ability of ZIKV to vertically transmit in its competent vectors like Aedes aegypti and Aedes albopictus helps it to cope with adverse conditions. This could be the reason for its major outbreak from time to time. As ZIKV outbreak can become a global threat worldwide so, to fight against its outbreaks there is a need for safe and effective drugs and vaccines to fight against it. In more than 80% of cases, ZIKV infection is asymptomatic and leads to complications like microcephaly in newborn and Guillain-Barré syndrome (GBS) in adults. The drugs like sofosbuvir, chloroquine, and suramine were found to be effective against ZIKV but needs further evaluation tests for their safety measures in pregnant women. Although Temoporfin can be given to pregnant women but needs to be test further for its side effects. Many vaccine types based on protein, vector, DNA, mRNA were formulated. Some like mRNA-1325, VRC-ZKADNA090-00-VP have reached phase II of clinical trials. Some new techniques should be used for formulation and testing the efficacy of vaccines. As there are no recent outbreaks of ZIKV several studies have shown continuous circulation of ZIKV in mosquito vectors and there are chances of re-emergence of ZIKV near future. So, the vaccines and drugs should be tested further and a safe, effective therapeutics techniques should be licensed to be used at the time of outbreak.